OXIDATIVE MODIFICATION OF PROTEINS AND SPECIFIC SUPEROXIDE DISMUASE ACTIVITY OF DESULFUROMONAS ACETOXIDANS ІМV В-7384 BACTERIA UNDER THE INFLUENCE OF FERRIC CITRATE - О. Д. Масловська; С. О. Гнатуш (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2015)
Aim. Investigation of oxidative modification of proteins and specific superoxide dismutase activity of Desulfuromonas acetoxidans ІМV В-7384 bacteria under the influence of ferric citrate. Methods. Generation of protein carbonyl groups (CG) were determined in reaction with 2,4- dinitrophenylhydrazine. Specific superoxide dismutase activity was measured by the ability of enzyme to inhibit autoxidation of quercetin at рН 10 in the presence of tetramethylethylenediamine. Results. The content of protein CG under the influence of ferric citrate changed in dependence of duration of bacterial cultivation. Under the influence of all investigated concentrations of ferric citrate on second and third days of cultivation no significant increase of protein CG in comparison with control sample was observed. The increase of content of protein CG by 2–4 times under the influence of metal salt was reached on the fourth day of cultivation. Addition of ferric citrate caused substantial enhancing of specific SOD activity. Under the influence of all investigated concentrations of ferric citrate specific SOD activity increased with enhancing of duration of cultivation. Conclusions. Accumulation of significant concentrations of CG in  acetoxidans ІМ -В7384  proteins under the influence of ferric citrate indicates free radical mechanism of damage of cell proteins. Under these conditions neutralization of reactive oxygen species in D. acetoxidans ІМV-В7384 bacteria is evidently made by the enzymes of antioxidative defense system, including SOD.